2019
DOI: 10.1002/elps.201900134
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the full set of methylated β‐cyclodextrins as chiral selectors in capillary electrophoresis

Abstract: Comparative analysis of the full set of methylated ␤-cyclodextrins as chiral selectors in capillary electrophoresisThe chiral separation ability of the full library of methylated-␤-cyclodextrins towards pharmacologically significant racemic drugs including basic compounds was studied by chiral CE. The syntheses of all the methylated, single isomer ␤-cyclodextrins were revised and optimized and the aqueous solubility of the derivatives was unambiguously established. The three most relevant commercially availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 32 publications
(39 reference statements)
0
27
0
Order By: Relevance
“…Acetylation of CDs represents a very interesting synthetic tool for understanding chiral recognition mechanisms [6, 10]. This is because it has been observed that the chiral recognition ability of acetylated CDs commonly improves if compared to their native precursors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Acetylation of CDs represents a very interesting synthetic tool for understanding chiral recognition mechanisms [6, 10]. This is because it has been observed that the chiral recognition ability of acetylated CDs commonly improves if compared to their native precursors.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of CE and NMR spectroscopy is a well‐established tandem for a better understanding the mechanisms of weak intermolecular interactions [1–13]. In particular, CE is not only a powerful separation technique but due to its high separation efficiency it also allows to detect those fine intermolecular interactions that are commonly invisible with other instrumental (separation or non‐separation) techniques.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The distributions of substitutions in different methylated β-CD derivatives are nicely illustrated in the Figure 1 of the following paper: (Varga et al, 2019). A precise determination of pH and the use of a pH reference standard in essential, because the CTZ chemiluminescence depends on pH.…”
Section: Methyl-beta-cyclodextrin Average Mw 1310 Acros Acrosmentioning
confidence: 91%